2016
DOI: 10.4196/kjpp.2016.20.6.565
|View full text |Cite
|
Sign up to set email alerts
|

The effects of paeoniflorin injection on soluble triggering receptor expressed on myeloid-1 (sTREM-1) levels in severe septic rats

Abstract: Paeoniflorin (PAE) is the most abundant compound in Xuebijing injection widely used to treat sepsis. We aimed to investigate effect of PAE on expression of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) in a rat model of sepsis. Wistar rats were divided into Normal, Model, and PAE groups (n=20 each). Endotoxin was administrated at 5 mg/ml/kg in Model and PAE rats to establish rat sepsis model. 1 h after endotoxin administration, PAE was administrated at 4 ml/kg in PAE group once per day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…No significant differences were observed between C0127 and C0127-2 group, suggesting paeoniflorin and HSYA are the core compounds in XBJ for cardiac protection. Two previous studies suggested paeoniflorin rendered cardiac protection in LPS-induced endotoxemia models (Zhai and Guo, 2016b;Liu et al, 2016). Liu et al found 12 mg/kg paeoniflorin once/day reduced plasma CK-MB (a biomarker of severe heart damage) to normal level 72 h after the LPS administration (5 mg/kg) in a rat model (Liu et al, 2016).…”
Section: C0127s Improved the Cardiac Function Of Septic Micementioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were observed between C0127 and C0127-2 group, suggesting paeoniflorin and HSYA are the core compounds in XBJ for cardiac protection. Two previous studies suggested paeoniflorin rendered cardiac protection in LPS-induced endotoxemia models (Zhai and Guo, 2016b;Liu et al, 2016). Liu et al found 12 mg/kg paeoniflorin once/day reduced plasma CK-MB (a biomarker of severe heart damage) to normal level 72 h after the LPS administration (5 mg/kg) in a rat model (Liu et al, 2016).…”
Section: C0127s Improved the Cardiac Function Of Septic Micementioning
confidence: 99%
“…A series of studies indicated these two compounds are promising Xuebijing constituents of therapeutic importance (Cao et al, 2011;Zhai and Guo, 2016b;Cheng et al, 2016;Zou et al, 2018;Shang et al, 2019). Paeoniflorin improved survival and cardiac function in LPS-treated rodents (Cao et al, 2011;Zhai and Guo, 2016b;Liu et al, 2016). HSYA improved ischaemiainduced cardiac haemodynamics by stimulating nucleolinmediated angiogenesis (Zou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is found to be associated with the development of acute kidney injury (AKI) [ 2 ]. Bacterial infections, most commonly due to Gram-negative bacteria and their endotoxins, are the most common underlying cause of sepsis [ 1 3 ]. Inflammation associated with sepsis involves a dynamic response of vascularized tissue to injury [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections, most commonly due to Gram-negative bacteria and their endotoxins, are the most common underlying cause of sepsis [ 1 3 ]. Inflammation associated with sepsis involves a dynamic response of vascularized tissue to injury [ 3 ]. In the inflamed tissues, changes in blood flow, vascular permeability, leukocyte accumulation, and edema occur, with a variety of mediators being involved in this chain of events [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation